Wieloznaczna semantyka czerni w „Metamorfozach” Owidiusza - Czapińska-Bambara, Marta; Danek, Zbigniew (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
The subject of this study is how and in what scope Ovid uses the terms of blackness (ater, niger, pullus, piceus, fuscus) occurring in Latin in his Metamorphoses. Particular attention is paid to those places in the poem where this blackness enhances the dynamics of the situations described by the poet, gaining at the same time a specific axiological qualification, and also justifies through its presence the conventional use of the colour as an expression of mourning. This non-typical usage of the terms mentioned above leads to the conclusion that in this aspect of his poetic creativity, Ovid depicts the mythical reality he presents in an absolutely non-imitative manner, but rather full of at times surprising expressionistic colour associations.The subject of this study is how and in what scope Ovid uses the terms of blackness (ater, niger, pullus, piceus, fuscus) occurring in Latin in his Metamorphoses. Particular attention is paid to those places in the poem where this blackness enhances the dynamics of the situations described by the poet, gaining at the same time a specific axiological qualification, and also justifies through its presence the conventional use of the colour as an expression of mourning. This non-typical usage of the terms mentioned above leads to the conclusion that in this aspect of his poetic creativity, Ovid depicts the mythical reality he presents in an absolutely non-imitative manner, but rather full of at times surprising expressionistic colour associations.